Fungal Lactamases: Their Occurrence and Function - Gao, Minglu; Glenn, Anthony E.; Blacutt, Alex A.; Gold, Scott E. (Frontiers in Microbiology, 2017)
Fungi are absorptive feeders and thus must colonize and ramify through their substrate to survive. In so doing they are in competition, particularly in the soil, with myriad microbes. These microbes use xenobiotic compounds as offensive weapons to compete for nutrition, and fungi must be sufficiently resistant to these xenobiotics. One prominent mechanism of xenobiotic resistance is through production of corresponding degrading enzymes. As typical examples, bacterial β-lactamases are well known for their ability to degrade and consequently confer resistance to β-lactam antibiotics, a serious emerging problem in health care. We have identified many fungal genes that putatively encode proteins exhibiting a high degree of similarity to β-lactamases. However, fungal cell walls are structurally different from the bacterial peptidoglycan target of β-lactams. This raises the question, why do fungi have lactamases and what are their functions? Previously, we identified and characterized one Fusarium verticillioides lactamase encoding gene (FVEG_08291) that confers resistance to the benzoxazinoid phytoanticipins produced by maize and several other grain crop species. Since benzoxazinoids are γ-lactams with five-membered rings rather than the four-membered β-lactams, we refer to the predicted enzymes simply as lactamases, rather than β-lactamases. An overview of fungal genomes suggests a strong positive correlation between environmental niche complexity and the number of fungal lactamase encoding genes, with soil-borne fungi showing dramatic amplification of lactamase encoding genes compared to those fungi found in less biologically complex environments. Remarkably, Fusarium species frequently possess large (>40) numbers of these genes. We hypothesize that many fungal hydrolytic lactamases are responsible for the degradation of plant or microbial xenobiotic lactam compounds. Alignment of protein sequences revealed two conserved patterns resembling bacterial β-lactamases, specifically those possessing PFAM domains PF00753 or PF00144. Structural predictions of F. verticillioides lactamases also suggested similar catalytic mechanisms to those of their bacterial counterparts. Overall, we present the first in-depth analysis of lactamases in fungi, and discuss their potential relevance to fitness and resistance to antimicrobials in the environment.